2021
DOI: 10.1097/mpg.0000000000003338
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Mast Cell Distribution in the Gastrointestinal Tract of Children

Abstract: Objectives: The physiological number and distribution of mast cells (MCs) in the pediatric gastrointestinal (GI) tract is not well defined and reference values of normality are missing. To define a physiological and disease defining cut-off, a systematic histological exploration of MC distribution from the esophagus to the rectum in healthy as well as in patients with gastrointestinal food allergies (GFA) was performed. Methods: Nine pediatric subjects that exhibited unremarkable histopathological evaluations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The findings in these and several other studies 27,[32][33][34][35][36] that report mean mast cell counts in excess of 20/hpf at various sites in the GI tract suggest that (1) the proposed upper limit of normal of 20/HPF for mast cells in GI biopsies is not applicable to biopsies stained with CD117, and (2) there is insufficient evidence to support mast cell counting in GI biopsies as part of the diagnostic work-up for chronic diarrhoea with no identified underlying cause.…”
Section: Mast Cell Activation Syndromesupporting
confidence: 66%
“…The findings in these and several other studies 27,[32][33][34][35][36] that report mean mast cell counts in excess of 20/hpf at various sites in the GI tract suggest that (1) the proposed upper limit of normal of 20/HPF for mast cells in GI biopsies is not applicable to biopsies stained with CD117, and (2) there is insufficient evidence to support mast cell counting in GI biopsies as part of the diagnostic work-up for chronic diarrhoea with no identified underlying cause.…”
Section: Mast Cell Activation Syndromesupporting
confidence: 66%
“…Our utilization of having subjects with polyps or reflux as our control cohort without any evidence of chronic abdominal pain, changes in bowel habits, and histological inflammation are not unique as these criteria have been used for control cohorts previously in both adult and pediatric literature ( 16 , 17 , 22 , 23 ). For instance, Jakate et al selected 50 subjects with non-diarrheal conditions (such as duodenal biopsies for gastroesophageal reflux, Helicobacter gastritis , gastric fundic gland polyps, and mucosa adjacent to duodenal adenomatous polyps; and colonic biopsies for melanosis and mucosa adjacent to adenomatous polyps) as their control group.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective selection of the control cohort was performed in a manner similar to previously published adult and pediatric studies (13,(16)(17)(18)(21)(22)(23). Controls were children aged 8 to 21 years old with a known diagnosis of polyposis syndrome, rectal bleeding, and/or gastroesophageal reflux who had previously undergone upper and/or lower endoscopies between January 2017 and September 2021 and had normal histology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal mast cells are found throughout the gastrointestinal tract and normally account for 2-3% of mononuclear cells in the lamina propria. Ehrsam et al [37] have recently reported the number and distribution of mast cells in the pediatric gastrointestinal tract in healthy individuals, as well as in patients with food allergies. Importantly, mast cell hyperplasia and higher tryptase concentrations in the intestinal mucosa are associated with allergic inflammation of the mucosa in patients with food allergies and IBS [38,39].…”
Section: Human Mast Cell Subtypesmentioning
confidence: 99%